2017
DOI: 10.1002/jcp.25989
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid is necessary for proliferation and differentiation of C2C12 myoblasts

Abstract: Folic acid, a water soluble B vitamin, plays an important role in cellular metabolic activities, such as functioning as a cofactor in one-carbon metabolism for DNA and RNA synthesis as well as nucleotide and amino acid biosynthesis in the body. A lack of dietary folic acid can lead to folic acid deficiency and result in several health problems, including macrocytic anemia, elevated plasma homocysteine, cardiovascular disease, birth defects, carcinogenesis, muscle weakness, and walking difficulty. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 46 publications
2
28
0
1
Order By: Relevance
“…This apparent inconsistency might be explained in part by our previous observation that the inhibition of such differentiation by PDZRN3 depletion is mediated by the up-regulation of Id2 16 . DNA damage before the induction of myoblasts to myotubes differentiation has also been shown to inhibit the differentiation process 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…This apparent inconsistency might be explained in part by our previous observation that the inhibition of such differentiation by PDZRN3 depletion is mediated by the up-regulation of Id2 16 . DNA damage before the induction of myoblasts to myotubes differentiation has also been shown to inhibit the differentiation process 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Replenishing the intracellular folate pool by the intake of exogenous folates, such as folic acid, is especially important for rapidly dividing cells, including cancer cells. Ample preclinical evidence links cellular replication to folate availability [16][17][18][19][20][21][22][23]. Such a link raised the concern that excessive consumption of dietary folate or folic acid may promote the progression of neoplastic lesions and increase the risk of malignancies and cancer-related death [11,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have explicitly reported that MondoA is involved in myoblast differentiation. The myogenic genes MyHC, MyoG, and IGF2 are necessary for driving early and late skeletal muscle differentiation [ 30 31 ]. We demonstrated that the transcription factor MondoA promotes myoblast differentiation by increasing the expression of these myogenic genes.…”
Section: Discussionmentioning
confidence: 99%